Cholinergic facilitation of neurotransmission to the smooth muscle of the guinea-pig prostate gland - Lau, W A K (2000)
1. Functional experiments have been conducted to assess the effects of acetylcholine and carbachol, and the receptors on which they act to facilitate neurotransmission to the stromal smooth muscle of the prostate gland of the guinea-pig. 2. Acetylcholine and carbachol (0.1 μM–0.1 mM) enhanced contractions evoked by trains of electrical field stimulation (20 pulses of 0.5 ms at 10 Hz every 50 s with a dial setting of 60 V) of nerve terminals within the guinea-pig isolated prostate. In these concentrations they had negligible effects on prostatic smooth muscle tone. The facilitatory effects of acetylcholine, but not those of carbachol, were further enhanced in the presence of physostigmine (10 μM). 3. The facilitatory effects of carbachol were unaffected by the neuropeptide Y Y(1) receptor antagonist BIBP 3226 ((R)-N(2)-(diphenylacetyl)-N-[(4-hydroxyphenyl)methyl]-argininamide) (0.3 μM, n=3) or suramin (100 μM, n=5). Prazosin (0.1 μM, n=5) and guanethidine (10 μM, n=5) alone and in combination (n=4), reduced responses to field stimulation and produced rightward shifts of the log concentration-response curves to carbachol. 4. The rank orders of potency of subtype-preferring muscarinic receptor antagonists in inhibiting the facilitatory actions of acetylcholine and carbachol were: pirenzepine > HHSiD (hexahydrosiladifenidol) > pF-HHSiD (para-fluoro-hexahydrosiladifenidol)⩾ 5 himbacine, and pirenzepine > HHSiD > himbacine⩾ 5 pF-HHSiD, respectively. These profiles suggest that muscarinic receptors of the M(1)-subtype mediate the facilitatory effects of acetylcholine and carbachol on neurotransmission to the smooth muscle of the guinea-pig prostate.